The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2011
DOI: 10.5137/1019-5149.jtn.3927-10.2
|View full text |Cite
|
Sign up to set email alerts
|

A morphometric study of foramen ovale

Abstract: AIm:To note the morphological variations and morphometric details of foramina ovale in dry adult skulls of Indian origin. mAterIAl and methOds: 82 dry adult human skulls of unknown sex and of Indian origin were obtained and variations in appearance and number of foramen ovale were noted. The length and width of the foramina ovale of both sides were determined using digital Vernier calipers and area (A) was also calculated and analyzed.results: Out of 82 adult skulls, the values for the right side was 7.64 ± 1.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
34
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(42 citation statements)
references
References 8 publications
4
34
1
1
Order By: Relevance
“…Other forms represent 4-5%. This comes in accordance with previous studies done by Yanagi (1987) and Somesh et al (2011), as the oval shape was the common, then the almond shape.…”
Section: Discussionsupporting
confidence: 93%
“…Other forms represent 4-5%. This comes in accordance with previous studies done by Yanagi (1987) and Somesh et al (2011), as the oval shape was the common, then the almond shape.…”
Section: Discussionsupporting
confidence: 93%
“…There are some studies which indicates the abnormal morphology of the Foramen ovale, such that it can be occasionally covered by ossified ligaments stretching between the lateral pterygoid process and the sphenoid spine or its venous part may be compartmentalised by a bony spur located antero-medially resulting in doubled Foramen ovale [7]. An atypical position of foramen ovale and neighbouring osseous structures could influence the anatomical organisation of the nerves that run through this opening.…”
Section: Discussionmentioning
confidence: 99%
“…The mean length of the foramen ovale is about 3.85 mm in the newborn and about 7.2 mm in adults and its width extends from 1.81 mm in the newborn to 3.7 mm in case of adults. [6,7].Knowledge of topography and variations of the foramen ovale can prevent injury to the trigeminal nerve during surgical approaches.Therefore the study has been undertaken to know the difference in linear measurements of right and left foramen ovale in human skulls of Indian origin.…”
Section: Introductionmentioning
confidence: 99%
“…It is a reasonable assumption that any change of the volume and shape of the venous plexus may alter FO shape and size. Searching the literature, variability exists as regards the FO types of shape (oval, truly oval, elongated oval, elongated, semicircular, almond, round, rounded, slit, irregular, D shape and pear) [7,23,37] and FO size (length and width) among studies. As regards FO length, the higher values were recorded by Patil et al [27] and Murugan and Saheb [22], while lower values were found by Kaplan et al [16], Natsis et al [23], Lang et al [17] and Agarwal and Gupta [1].…”
Section: Introductionmentioning
confidence: 99%